Electrocardiographic Alterations of Dilated Cardiomyopathy in Dogs - Srivastava, Mukesh K.; Ahuja, Anil; Velhankar, R.D.; Srivastav, Ashish; Tiwari, Jitendra; Sharma, Barkha; Raikwar, Arpana (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
The study encompassed 2497 dogs, identifying 29 cases of Dilated Cardiomyopathy (DCM). Electrocardiographic (ECG) evaluations revealed significant differences in key parameters between DCM-affected and healthy dogs. Notably, dogs with DCM exhibited alterations in P wave amplitude and duration, QRS duration, and R wave amplitude, indicative of cardiac dysfunction. Proportional analysis further delineated distinct ECG abnormalities specific to left and bilateral DCM presentations. In left DCM, increased QRS and P wave duration, and elevated R wave amplitude were predominant, while bilateral DCM displayed similar anomalies alongside low voltage QRS and non-measurable P wave. Increased P wave duration was prevalent in both forms of DCM, with atrial fibrillation rendering P waves non-measurable in a notable proportion. Deep Q wave presence substantiated DCM diagnosis. Furthermore, dogs with left and bilateral DCM exhibited prolonged QRS duration, indicative of cardiac enlargement and global myocardial degeneration. Low voltage QRS complexes indicated potential pericardial effusion or ascites. However, PR and QT intervals did not significantly differentiate between healthy and DCM-affected canines. Rhythm disturbances were prevalent in DCM, with atrial fibrillation most common, followed by ventricular premature complexes, sinus arrhythmia, and other variants. Left bundle branch block and diverse degrees of AV block and electrical alternans were also detected. Proportional analysis delineated varied prevalence rates of rhythm abnormalities between left and bilateral DCM groups, reflecting nuanced pathological distinctions. This comprehensive investigation underscores the pivotal role of ECG assessments in diagnosing and monitoring DCM in canine populations, elucidating specific electrocardiographic aberrations associated with distinct DCM presentations.